Peran Prilaku keuangan dalam memediasi literasi keuangan dan inklusi keuangan terhadap kinerja umkm di kota Cirebon - Dwi Setiani; Yunita Indah Pratiwi; Acep Komara (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to analyze the role of financial behavior in mediating the influence of financial literacy and financial inclusion on the performance of MSMEs in Cirebon. This research is quantitative descriptive, primary data. The Partial Least Square (PLS) testing method is based on Structural Equation Modeling (SEM) with the Non-Probability Sampling method with purposive sampling as sample collection. The population in this research is MSME actors in Cirebon City with a sample of 61 micro business actors with a scale for measuring respondents' opinions using Likert. This research shows the following results: First, financial literacy has a negative and insignificant effect on the performance of MSMEs. Second, Financial Inclusion has a positive but not significant effect on MSME performance. Third, Financial Behavior has a positive and significant effect on MSME Performance. Fourth, Financial Literacy has a positive and significant effect on Financial Behavior. Fifth, Financial Inclusion has a positive but not significant effect on Financial Behavior. Sixth, financial behavior has a positive and significant effect in mediating financial literacy on MSME performance. Seventh, financial behavior has a positive and insignificant effect in mediating financial inclusion on MSME performance. This research shows that increasing understanding of financial literacy and knowledge of access to financial services accompanied by good financial behavior and appropriate and wise implementation by MSME players can improve MSME performance.